Dampak Pengembangan Objek Wisata Pantai Takisung terhadap Pendapatan Pedagang dan Masyarakat Lokal di Kabupaten Tanah Laut - Awalia, Uminor (PPJP ULM, 2018)
The purpose of this research is to know the impact of the development of Takisungbeach tourism object to the income of traders and local communities in Tanah LautDistrict. The method of data collection starts from observation, interviews with therespondents, and the Department of Tourism, and documentation. The further researchresult is analyzed by quantitative descriptive method and data processing techniques withfrequency distribution. The result of the research shows that the impact of the development of Takisungbeach tourism object initially impacts on the income of traders and local communities,adding new jobs, but since the last two years, the development of Takisung beach tourismobject has less impact on income, the income of traders and local communitiesdecreased, and it is caused by the number of new tourism objects, especially beaches inTanah Laut District. Therefore it is causing visitors to switch to other tourism objects.Thus the income of traders and local communities who participate in the use of the beachalso declined.